Using computer simulation to study the dynamics of moisture distribution in wood / Mohd Ariff Jamaludin ... [et al.] - Jamaludin, Mohd Ariff; Hong, Yan Leng; Bokhari, Semsolbahri; Midon, Shokari; Nordin, Kamamlzaman; Ahmad, Mansur (2004)
The mechanism of moisture movement through wood has been extensively studied because of its fundamental importance in understanding the behaviour of wood during processing and when it is in service. However, most studies were done using conventional experimental methods which sometimes can be tedious, time consuming and destructive where materials are wasted. Computer simulated studies allow shorter lead time and also reduced greatly destructive analysis of test specimen. Theoretically, it is possible to trace the movement of moisture in timbers through heat or mass transfer analysis or both. In this study, the dynamic profiles of moisture movement in a tree trunk were determined at a series of tree heights using the finite element method (FEM) of steady-state heat transfer analysis. An Acacia mangium tree was selected from an Acacia mangium plantation of 6 - 15 years of age in Serdang, Malaysia to study the moisture distribution and height relationship. It was deduced from the results that the moisture movement at the butt-end of the tree was higher than the moisture movement at the lop of the tree. The resulting numerical solutions (FEM) matched well with experimental results. It can be concluded that computer simulation can be an excellent tool for future lumber drying research, such as mapping induced drying stresses to analyse checking and warping in kiln dried timbers.